Sport-Orthopädie - Perret C; 2; Flueck JL (Deutsche Zeitschrift für Sportmedizin, 2016)
Purpose: Supplement use has gained increasing interest in the past decade includingin Paralympic sports. However, several physiological differences (e.g. prolonged gastrointestinal transition time, reduced resting energy expenditure) existbetween able-bodied and athletes with a spinal cord-injury due to the impairment of the autonomic nervous system, which might influence supplement effects. The aim of this review was to investigate the impact of supplement use on exercise performance in spinal cord-injuredathletes.Methods: A comprehensive review was performed using Pubmed as search engine to detect studies investigating supplement use in spinal cord-injuredathletes.Results: Only five studies were identified. These studies dealt with the use of carbohydrates, creatine, caffeine, sodium citrate or the combination of the latter two supplements. One study using an11% carbohydrate solution found an endurance performance enhancing effect. Caffeine seemed to have ergogenic effects on sprint and short-term but not on endurance performance in athletes with a para- or tetraplegia. Sodium citrate and creatine showed no performance enhancing effects.Conclusions: The results showed that results from studies performed with able-bodied individualscannot be transferredinto a wheelchair sport context. Evidence-based recommendations on supplement use are not feasible due to the lack of data from spinal cord-injuredathletes. This means that individually tailored solutions for each wheelchair athlete are necessaryfor supplement use at present and further studies are needed to gain more evidence-based information.KEY WORDS: Sports Nutrition, Paraplegia, Elite Sport, Caffeine, Creatine